Anisotropy of Magnetic Susceptibility and Rock Magnetic Applications in the Deccan Volcanic Province based on some Case Studies - Sangode, S.J.; Sharma, Rajiv; Mahajan, Rasika; Basavaiah, N.; Srivastava, Priyeshu; Gudadhe, Swapnil S.; Meshram, D.C.; Venkateshwarulu, M. (My University, 2017)
Anisotropy of Magnetic Susceptibility (AMS) as a tool has been explored here to investigate the nature of petrofabrics in Deccan Volcanic Province (DVP) of west-central Indian region by representative sampling in typical pahoehoe and rubbly pahoehoe lava flows, dykes within flows, shear zone and the impact crater units. The rock magnetic analysis indicate varying degree of concentration of titanomagnetite compositions dominated by multi domain (MD) to pseudo single domain (PSD) grains favoring shape anisotropy of minerals that form primary fabrics. The pahoehoe type lava flows shows planar oblate fabrics without any preferred orientation of principle susceptibility axis (K1 ) depicting crystal settling (of magnetic grains) as chief mechanism of fabric development. The rubbly pahoehoe type lava flow exhibit prolate fabrics with well clustered maximum susceptibility axis within horizontal to sub-horizontal planes depicting their response to viscosity shear. The dykes show well clustered K1 parallel to it’s plane locked during rapid contractional cooling. The sampling at Lonar impact crater was unable to trace any clear fabric due to impact/shock induced deformation and rather preserve the primary fabrics. Further, the shear zone depict random fabrics demanding more detailed and systematic sampling in both the cases. The present investigation infer that the magnetic mineralogy and magnetic fabric variations in the DVP are controlled by the flow mechanism and style of cooling that is characteristic of the given flow unit or dyke and any secondary or superimposed fabric needs to be examined by critical sampling strategy. While more detailed attempts are required to establish the AMS as a tool to record various aspects including the flow dynamics and rate of effusion in the vast terrain of DVP; the present approach is useful to characterize and correlate the lava flow units and dyke occurrences.
Keywords: Deccan volcanic province; Rock magnetic applications; Magnetic suceptibility